THE MOST IMPORTANT ROLE OF VITAMIN C IN THE HUMAN BODY (Web of Teachers: Inderscience Research, 2023)
This article discusses the most important role of vitamin C in the human body. Vitamin C is important in the prevention of many diseases in the human body and in maintaining a healthy lifestyle. Therefore, it is important for everyone, without exception, to get the right amount of vitamin C.